The ELL teacher's toolbox : hundreds of practical ideas to support your students - Ferlazzo, Larry; Hull-Sypnieski, Katie, 1974- (San Francisco, CA : Jossey-Bass, a Wiley brand, 2018)
Practical strategies to support your English language learners The ELL Teacher's Toolbox is a practical, valuable resource to be used by teachers of English Language Learners, in teacher education credential programs, and by staff development professionals and coaches. It provides hundreds of innovative and research-based instructional strategies you can use to support all levels of English Language Learners. Written by proven authors in the field, the book is divided into two main sections: Reading/Writing and Speakingstening. Each of those sections includes'Top Ten' favorites and between 40 and 70 strategies that can be used as part of multiple lessons and across content areas. -Contains 60% new strategies -Features ready-to-use lesson plans -Includes reproducible handouts -Offers technology integration ideas The percentage of public school students in the U.S. who are English language learners grows each year-and with this book, you'll get a ton of fresh, innovative strategies to add to your teaching arsenal.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on April 30, 2018).
Keywords: English language -- Study and teaching -- Foreign speakers -- Handbooks, manuals, etc; LANGUAGE ARTS & DISCIPLINES -- General; English language -- Study and teaching -- Foreign speakers; Electronic books; Handbooks and manuals